2001
DOI: 10.1104/pp.126.3.1139
|View full text |Cite
|
Sign up to set email alerts
|

NAD Malic Enzyme and the Control of Carbohydrate Metabolism in Potato Tubers

Abstract: Potato (Solanum tuberosum) plants were transformed with a cDNA encoding the 59-kD subunit of the potato tuber NAD-dependent malic enzyme (NADME) in the antisense orientation. Measurements of the maximum catalytic activity of NADME in tubers revealed a range of reductions in the activity of this enzyme down to 40% of wild-type activity. There were no detrimental effects on plant growth or tuber yield. Biochemical analyses of developing tubers indicated that a reduction in NADME activity had no detectable effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 45 publications
(22 reference statements)
1
81
0
1
Order By: Relevance
“…Detailed biochemical characterization revealed that this was due to regulation of the activation state of the first committed step of starch synthesis that is catalyzed by AGPase (Centeno et al, 2011). Intriguingly, however, this is not the first study to implicate reactions beyond the direct pathway of starch biosynthesis, since the mitochondrial NAD-ME (Jenner et al, 2001), the plastidial adenylate kinase (Regierer et al, 2002), and the cytosolic UMP synthase have been demonstrated to In our previous studies, we focused on mitochondrial reactions of the TCA cycle, and here, we evaluated the effect of modifying malate-pyruvate balances at different subcellular locations in a fruit ripening-specific manner by silencing either cytosolic PEPCK or the plastidic NADP-ME.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed biochemical characterization revealed that this was due to regulation of the activation state of the first committed step of starch synthesis that is catalyzed by AGPase (Centeno et al, 2011). Intriguingly, however, this is not the first study to implicate reactions beyond the direct pathway of starch biosynthesis, since the mitochondrial NAD-ME (Jenner et al, 2001), the plastidial adenylate kinase (Regierer et al, 2002), and the cytosolic UMP synthase have been demonstrated to In our previous studies, we focused on mitochondrial reactions of the TCA cycle, and here, we evaluated the effect of modifying malate-pyruvate balances at different subcellular locations in a fruit ripening-specific manner by silencing either cytosolic PEPCK or the plastidic NADP-ME.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considerable control has been demonstrated to be harbored by the plastidial adenylate and Glc-6-P transporter (Tjaden et al, 1998;Zhang et al, 2008), with a minor yet considerable proportion also vested in the plastidial phosphoglucomutase reaction . Studies beyond the direct pathway of starch biosynthesis also indicate important roles for the mitochondrial NADmalic enzyme (Jenner et al, 2001) and the plastidial adenylate kinase (Regierer et al, 2002). However, although the exact mechanism underlying this link in the former case has yet to be resolved, the latter has been characterized to affect both the substrate levels and activation status of the AGPase reaction (Oliver et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Of these reactions, although some of the control of starch synthesis resides in the plastidial phosphoglucomutase reaction (Fernie et al, 2001b), the AGPase reaction harbors the highest proportion of control within the linear pathway (Sweetlove et al, 1999;Geigenberger et al, 1999Geigenberger et al, , 2004. In addition, considerable control resides in both the Glc-6-P phosphate antiporter (Zhang et al, 2008) and the amyloplastidial adenylate transporter (Tjaden et al, 1998;Zhang et al, 2008) as well as in reactions external to the pathways, such as the amyloplastidial adenylate kinase (Regierer et al, 2002), cytosolic UMP synthase (Geigenberger et al, 2005), and mitochondrial NAD-malic enzyme (Jenner et al, 2001).…”
mentioning
confidence: 99%
“…Another feature associated with the TCA cycle in plants, but not found in other organisms, is related to the significant activity of NAD-dependent malic enzyme (NAD-ME) or malate oxidoreductase, responsible for catalyzing the oxidative decarboxylation of malate to pyruvate, finally allowing complete oxidation of malate (Jenner et al, 2001). …”
Section: Tricarboxylic Acid Cycle In Plantsmentioning
confidence: 99%